DEIXIS IN MARK ZUCKERBERG’S HARVARD COMMENCEMENT SPEECH - Sihura, Candra (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2023)
This research deals with the analysis of deixis in Mark Zuckerberg’s Harvard commencement speech. Deixis is the study of pragmatics that concerns with the interpretation of utterances that relates to people, place, time, and the sign of the speaker or the area in the discourse. The objectives of this research were to find out the types of deixis in Mark Zuckerberg’s Harvard commencement speech and the references of deixis found in Mark Zuckerberg’s Harvard commencement speech. This research was conducted by applying descriptive qualitative method. The data was analyzed by using Miles & Huberman’s theory such as data reduction, data display, conclusion drawing and verification. The result of this research shows that there were found five types of deixis in Mark Zuckerberg’s Harvard commencement speech such as person deixis, place deixis, time deixis, discourse deixis and social deixis. The results showed that each deixis has different references based on the context of their use in the speech. Based on the research finding, it is concluded that deixis is inseparable in human life because people always use deixis in daily communication. Deixis is imperative to learn because it help people to understand the meaning of every utterance conveyed by the speaker.